THE PHENOMENON OF GRADUATION IN SHAVKAT RAHMAN'S POETRY - Ruziyeva Son Egamberdiyevna; Egamberdiyeva Son Jonibekovna; Khaitov Husniddin Hasanovich (Galaxy International Interdisciplinary Research Journal, 2023)
This in the article Uzbek modern poetry manifestation a poet Shaukat Rahman's some in his poems encountered gradation to the event about feedback statement done _ In this of the poet in his poems gradation to the event circle clauses separate art is taken increasing place in particular scientific and theoretical analyses given .